Retrospecting Polish Audio Engineering Society Membership on 20th Anniversary of the Polish Section of the Audio Engineering Society - KOSTEK, Bozena; SANKIEWICZ, Marianna (Archives of Acoustics, 2011)
In this article some key events concerning founding Polish Section of the Audio Engineering Society were presented. In addition, the history covering International Symposia on Sound Engineering and Mastering was outlined. Also, papers contained in this issue were shortly reviewed.